An Open-Label, Rater-Blinded, 8-Week Trial of Bupropion Hydrochloride Extended-Release in Patients with Major Depressive Disorder with Atypical Features - Seo, H.-J.; Lee, B. C.; Seok, J.-H.; Jeon, H. J.; Paik, J.-W.; Kim, W.; Kwak, K.-P.; Han, C.; Lee, K.-U.; Pae, C.-U. (Pharmacopsychiatry, 2013)
The present study aimed at investigating the effectiveness and tolerability of bupropion hydrochloride extended release (XL) in major depressive disorder (MDD) patients with atypical features (AF).51 patients were prescribed bupropion XL for 8 weeks (6 visits: screening, baseline, weeks 1, 2, 4 and 8). The primary efficacy measure was a change of the Structured Interview Guide for the Hamilton Depression Rating Scale-Seasonal Affective Disorder Version (SIGH-SAD) from baseline to endpoint. Secondary efficacy measures included the SIGH-SAD atypical symptoms subscale, Clinical Global Impression–Severity (CGI-S), Sheehan Disability Scale (SDS) and Epworth Sleepiness Questionnaire (ESQ). Response or remission was defined as ≥50% reduction or ≤7 in SIGH-SAD total scores, respectively, at end of treatment.The HAM-D-29 total score reduced by 55.3% from baseline (27.3±6.5) to end of treatment (12.2±6.3) (p<0.001). Atypical symptom subscale scores also reduced by 54.5% from baseline (9.2±3.0) to end of treatment (4.2±2.8) (p<0.001). At the end of treatment, 24.4% (n=10) and 51.2% (n=21) subjects were classified as remitters and responders, respectively. The most frequently reported AEs were headache (13.7%), dry mouth (11.8%), dizziness (9.8%), and dyspepsia (9.8%).Our preliminary study indicates that bupropion XL may be beneficial in the treatment of MDD with atypical features. Adequately powered, randomized, double-blind, placebo-controlled trials are necessary to determine our results.
Keywords: bupropion XL; atypical depression; effectiveness; remission; response; tolerability